IMPACT OF ORGANIZATIONAL FAILURE OF RELEVANCE CONSOLIDATED BUDGET - Milojević, Ivan; Mihajlović, Milan; Cvijanović, Marko (Economics of Agriculture, 2012)
Financial concept of consolidated treasury account includes integration of basic factors of the business systems budget and other public funds. In this way established the relevance of the organizational structure of the system causes a systematic approach to fully satisfy the request. Normative conflict with the actual situation of the organization of the budget system causes partial financial coverage of budgetary positions and the actual non-compliance with the bookkeeping records.